Recombinant expression and characterization of two isoforms of Anopheles gambiae laccase-2 - Sullivan, Lucinda I. (Kansas State University, 2009)
Laccases are multicopper oxidases that catalyze the oxidation of a broad range of substrates, typically phenols and anilines. Research on laccases in fungi, plants, and bacteria has indicated that they have roles in detoxification, pigmentation, wound healing, morphogenesis and lignin synthesis and degradation. However, there has been relatively little investigation on laccases that exist in insects or other invertebrates. Insects have multiple laccase genes, but the function of just one type is known; laccase-2 (Lac2) orthologs are required for tanning of newly synthesized exoskeleton. In the mosquito Anopheles gambiae and other insect species whose genomes have been sequenced, alternative exon splicing may generate two isoforms of Lac2. The objective of this study was to characterize the two isoforms of AgLac2. They are identical in their first 500 residues, but the carboxyl-terminal 262 residues derived from alternative exons are 81% identical. Recombinant Lac2A and Lac2B were expressed and purified. They are both glycoproteins of ~81 kDa, and both can oxidize the laccase substrate ABTS as well as the catechols, N-β-alanyldopamine (NBAD) and N-acetyldopamine (NADA). Lac2A and Lac2B with ABTS have pH optima of 5.0-5.5 and 4.5-5.0, respectively. The pH optima with NBAD and NADA are 5.5-6.5. The Km values (mM) for Lac2A and Lac2B with NBAD are 5.4 ± 2.1 and 5.0 ± 2.6, respectively. The Km values (mM) for Lac2A and Lac2B with NADA are 0.7 ± 0.2 and 1.4 ± 0.5, respectively. Thus, there is little difference between the isoforms in K[subscript]m for these two substrates. The K[subscript]m values do indicate that both isoforms have a greater affinity for the substrate NADA. The kcat values (s[superscript]-1) for Lac2A and Lac2B with NBAD are 14.2 ± 3.5 and 6.0 ± 1.8, respectively. The k[subscript]cat values (s[superscript]-1) for Lac2A and Lac2B with NADA are 2.4 ± 0.2 and 0.5 ± 0.04, respectively. The most apparent difference between the two isoforms detected in the study is that Lac2A was four-fold more active than Lac2B when NADA was used as a substrate. Although the two isoforms are very similar in their amino acid sequences, the differences in catalytic properties may indicate different roles in insect physiology.
Keywords: Laccase; Anopheles gambiae; Multicopper oxidase; Biology, Entomology (0353); Chemistry, Biochemistry (0487)